Using Video To Teach Listening at English Department in Fkip Unilak Pekanbaru - Destina Kasriyati (J-SHMIC : Journal of English for Academic, 2019)
This study aims to provide a more interesting video-shaped learning media to teach listening courses at FKIP University of Lancang Kuning to improve students' ability in understanding the information. This research was conducted in FKIP Unilak in the odd semester of the 2016/2017 academic year. The research method used classroom action research to find out how far the learning media can improve students’ ability and the factors that influence student listening ability. Then, technique of collecting data used interview, observation, and test. Based on the result of test instrument that there was improvement in students’ listening skill after applying video as learning media. It showed from the test result that first stage was obtained the lowest score, that was 58, the highest 76, the average 76. While students’ score in the second stage is the lowest 76 and the highest 80, while the average value of 86. This indicated that the student listening ability increases after applying video as learning media. Furthermore, the interview and observation result deal with the second research question that factors affecting listening ability are influenced by the media. The second factor is the strategy and learning materials used by the lecturers in delivering teaching materials in listening learning also greatly affected the students’ ability.